The 2007-2009 subprime crisis and the global public policy response - Leão, P. R.; Leão, E. R.; Bhimjee, D. C. P. (The Journal of European Economic History, 2017)
In this article, we look at the root causes of the 2007-2009 subprime financial crisis in the United States and the ensuing global economic crisis. We then examine how public authorities in advanced economies responded to the crisis. We emphasize that, from the very start, public policy developed along two complementary but distinct lines of intervention: (i) short-term macroeconomic management, and (ii) medium- to long-term reshaping of the financial regulatory framework. We find that the two sub-sets of policies were pursued at the global level and not simply at the national and/or regional level. Finally, we summarize the main risks that emerged as a consequence of the macroeconomic policy response to the crisis, namely high volumes of public debt, an uncertain inflation outlook and the possible development of bubbles in some asset markets.